Functional characterization of a plastidal cation-dependent O-methyltransferase from the liverwort Plagiochasma appendiculatum. (October 2015) - Xu, Rui-Xue; Zhao, Yu; Gao, Shuai; Zhang, Yu-Ying; Li, Dan-Dan; Lou, Hong-Xiang; Cheng, Ai-Xia
Graphical abstract: PaOMT1 was able to methylate phenylpropanoids, flavonoids and coumarins, with a preference for the flavonoid quercetin. Although the substrate selectivity and biochemical feature of PaOMT1 is similar to CCoAOMT-like enzymes, the sequence alignment results indicated PaOMT1 is closer to true CCoAOMT enzyme. Highlights: A caffeoyl CoA O -methyltransferase like protein (PaOMT1) was isolated from a liverwort. PaOMT1 showed substrate and positional promiscuity. PaOMT1 is located in the plastids. Abstract: Caffeoyl CoA O -methyltransferases (CCoAOMTs), known to be involved in phenylpropanoid metabolism and lignin synthesis, have been characterized from several higher plant species, which also harbor CCoAOMT-like enzymes responsible for methylation of a variety of flavonoids, anthocyanins, coumarins and phenylpropanoids. Here, a gene encoding a CCoAOMT ( PaOMT1 ) was isolated from a sequenced cDNA library of the liverwort species Plagiochasma appendiculatum, a species belonging to the Family Aytoniaceae. The full-length cDNA sequence of PaOMT1 contains 909 bp, and is predicted to encode a protein with 302 amino acids. The gene products were 40–50% identical to CCoAOMT sequences of other plants. Experiments based on recombinant PaOMT1 showed that the enzyme was able to methylate phenylpropanoids, flavonoids and coumarins, with a preference for the flavonoid quercetin (19 ). Although the substrate selectivity and biochemical feature of PaOMT1 is similar to CCoAOMT-like enzymes, the sequence alignment results indicated PaOMT1 is closer to true CCoAOMT enzymes. A phylogenetic analysis indicated that PaOMT1 is intermediate between true CCoAOMTs and CCoAOMT-like enzymes. The transient expression of a PaOMT1-GFP fusion in tobacco demonstrated that PaOMT1 is directed to the plastids. PaOMT1 may represent an ancestral form of higher plant true CCoAOMT and CCoAOMT-like enzymes. This is the first time an O -methyltransferase was characterized in liverworts.